2019
DOI: 10.1111/jocn.15039
|View full text |Cite
|
Sign up to set email alerts
|

Modelling factors of urinary incontinence in institutional older adults with dementia

Abstract: Aims and Objectives This study applied structural equation modelling to explore the relationships among agitated behaviours, depression, cognitive function and activities of daily living, as well as associations between these factors and urinary incontinence). Background A high prevalence of urinary incontinence is found among institutional older adults with dementia. People with urinary incontinence suffer from increased financial burden and social isolation and experience reduced quality of life. Design Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Studies recommend a multicomponent and personalized training approach for older adults with mobility limitations, cognitive impairment, and urinary incontinence [4,9,23,76]. Although exergames contribute to increased training motivation and can be used as an alternative to conventional training, current exergames fail to incorporate interventions for all required training components in one single session.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies recommend a multicomponent and personalized training approach for older adults with mobility limitations, cognitive impairment, and urinary incontinence [4,9,23,76]. Although exergames contribute to increased training motivation and can be used as an alternative to conventional training, current exergames fail to incorporate interventions for all required training components in one single session.…”
Section: Resultsmentioning
confidence: 99%
“…Mobility limitations, cognitive impairment, and urinary incontinence are particularly common in older adults [1], having a negative impact on their lives. Moreover, these conditions are associated with gait impairments, increased risk of falling, and all-cause mortality [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of incontinence in RACFs is multifactorial and is highly associated with impairments in cognition and physical function 14 . A recent model of risk factors associated with urinary incontinence (UI) among institutional older adults with dementia revealed UI in this population was significantly related to impaired ability to perform activity of daily living 15 . Indeed, in a population‐based study of 54 816 people aged 60 to 89 with dementia and an age‐gender stratified sample of 205,795 people without dementia, Grant et al, 16 found the adjusted rate ratio for first diagnosis of UI was 3.2 (2.7‐3.7) in men and 2.7 (2.3‐3.2) in women, and for fecal incontinence was 6.0 (5.1‐7.0) in men and 4.5 (3.8‐5.2) in women.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have implications for the occurrence of avoidable harm and patient outcomes during an acute admission; incontinence is a common risk factor for falls [26,27] and catheters are associated with high rates of urinary tract infections [28]. These factors are also associated with a greater nancial burden, prolonged hospitalisation, re-admission and increased mortality [29][30][31]. Incontinence can also be emotionally demeaning for patients [32] as well as being humiliating and embarrassing [33] and, combined with dementia, it increases the stigma [34] that PLWD already experience [35][36][37] which can have signi cant negative impacts on quality of life [38].…”
Section: Introductionmentioning
confidence: 99%